Revitalization of Fiqh Al-Bi'ah in the Implementation of Green Banking for Islamic Bank - Mohammad Farid Fad (Department of Islamic Economics, Islamic University of Indonesia, 2021)
The banking industry can play a role in a balanced manner between economic growth and environmental protection. This kind of banking is called green banking, a banking system that operates its business based on the principles of sustainable development to carry out environmentally friendly practices and reduce the carbon footprint of banking operations. This study aims to understand the philosophy of green banking and its implementation in an effort to revitalize the values of fiqh al-bi'ah. The type of method used in this research is a qualitative method. Meanwhile, in the analysis, researchers used descriptive-analytical methods to systematically analyze and analyze facts that are accurate and accurate. This study found that in green banking practice there is harmony with the principles of environmental fiqh, namely in the management of environmental preservation obligations. With carbon emission policies and financing of environmentally friendly projects, green banking can play a dual role, namely supporting national development and economic growth against mafsadat by protecting the environment from arbitrary exploration and exploitation activities.